Radiação (UV-C) na conservação de tomate ‘Pizzadoro’ orgânico colhido em dois estádios de maturação - Binoti, Raquel Mantovani [UNESP]; Daiuto, Érica Regina [UNESP]; Vieites, Rogério Lopes [UNESP]; Nuvolari, Cibelli Magalhães [UNESP]; Furlaneto, Karina Aparecida [UNESP]; Ramos, Juliana Arruda [UNESP]; Carvalho, Lídia Raquel de [UNESP] (My University, 2013)
The aim of this work was to evaluate the postharvest quality of organic tomato ‘Pizzadoro’ harvested at different maturation stages and subjected to ultraviolet (UV-C) radiation. The tomatoes in the stadiums green and 'once and for all' maturation were selected and exposed to the radiation in apparel with light UV-C during 5, 10, 15 and 20 minutes, constituting the treatments respectively T1, T2, T3 and T4. The treatment controls (T0) it was formed of tomatoes no exposed to the light UV-C. The tomatoes were stored in expanded polypropylene trays under refrigeration (10 ± 1ºC and 90 ± 5% relative humidity). The tomatoes in the green stadium were appraised during 25 days, and the tomatoes in the "once and for all" stadium for 18 days. After these periods commercialization simulation was accomplished, being the fruits maintained for 3 days for the green stadium and 2 days to the stadium “once and for all”, in room temperature (27± 1ºC and 80% relative humidity ).The evaluated analyses were the weight loss, respiratory activity, pH, tritable acidity (AT), soluble solids (SS), and maturation index. The weight loss was superior in the tomatoes during the storage period in room temperature. In the two maturation stadiums evaluated , the treatment whose tomatoes were exposedto the radiation in light UV-C during 20 min, provided better results demonstrating to smallest weight loss,smaller activity respiratory, larger time for the ripening and larger index maturation values.

O presente trabalho teve por objetivo avaliar a qualidade pós-colheita do tomate orgânico ‘Pizzadoro’ colhidoem dois estádios de maturação e submetidos á radiação ultravioleta (UV-C). Os tomates nos estádios dematuração verde e ‘de vez’ foram selecionados e expostos à radiação em aparelho com luz UV-C durante 5, 10,15 e 20 minutos, constituindo respectivamente os tratamentos T1, T2, T3 e T4. O tratamento controle (T0) foi formado de tomates não expostos à luz UV-C. Os tomates foram armazenados em bandejas de polipropileno expandido sob refrigeração (10±1ºC e 90±5% UR). Os tomates no estádio verde foram avaliados durante 25 dias, e os tomates no estádio “de vez” por 18 dias com intervalo de 5 dias para o estádio verde e de 3 dias para o estádio de vez. Após estes períodos foi realizada simulação de comercialização, sendo os tomates mantidos durante 3 dias para o estádio verde e 2 dias para o estádio ‘de vez’, em temperatura ambiente (27±1ºC e 80±5%UR). As análises realizadas foram perda de massa fresca, respiração, coloração, pH, sólidos solúveis (SS), acidez titulável (AT), e índice de maturação. A colheita no estádio imaturo permitiu a conservação dos tomates ‘ Pizzadoro’ por maior período. A perda de massa foi superior nos tomates durante o período de armazenamento em temperatura ambiente. Nos dois estádios de maturação avaliados, o tratamento cujos tomares foram expostos à radiação em luz UV-C durante 20 min, proporcionou melhores resultados demonstrando a menor perda de massa, menor atividade respiratória, maior tempo para o amadurecimento e maiores valores de índice de maturação.
Radiation (UV-C) in the conservation of organic ‘Pizzadoro’ tomato harvest at two maturations stadium
Keywords: Lycopersicon esculentum L.; Refrigeration; Postharvest; Lycopersicon esculentum L.; Refrigeração; Pós-colheita